INFORMATION SYSTEM DEVELOPMENT PROCESS AS A DECISION-MAKING SUPPORT IN MANAGEMENT - Hia, Era Era (Faculty of Science and Technology University of Pramita Indonesia, 2026)
Decision making is a form of election management activities of a set of alternative action that have been previously formulated to solve a problem. The types of decisions can be divided into two kinds of decision making is not programmed and programmed. A decision maker is making decisions throught the intelligence, design, and alternative option. While the decision making process of planning, research, analysis and conceptual design, design, construction, implementation, maintenance and documentation and adaptation.